Vegetação nativa como um ativo ambiental em programa de pagamento por serviços hidrológicos - Mendonça, Angela Maria (2021)
Brazil has a consistent and robust set of legal references aimed at the protection, preservation and maintenance of water resources and the environment, which provide a legal and constitutional basis for payments for environmental and hydrological services. The intensification of agriculture increases the use of water resources, conflicting, in some situations, with the supply of water in cities. Therefore, in population supply watersheds, it is highly recommended that land management focuses on the protection of water resources. To guarantee this protection, some efforts are being applied in hydrographic basins and in rural planning, such as the instrument of Payment for Environmental Services – PSA. Considering that the hydrological service is an environmental service, the objective of this thesis was to propose a methodology for the implementation of Payments for Hydrological Services (PSH), aiming to transform areas of environmental liabilities into environmental assets. The steps were considered: to develop a model for obtaining revenue that allows payment for the provision of hydrological services and maintenance of this program; develop a model for the valuation of hydrological services; present a comparison between input and output of resources, verifying the feasibility of implementing the PSH in population supply basins; propose a method to prioritize the PSH candidate properties. The case study was the water supply basin of the municipalities of Caiçara and Frederico Westphalen - RS, called Lajeado do Pardo, which has been studied since 2007. A Rapid Assessment Protocol - PAR was proposed for classification of properties that are candidates for the PSH, considering 17 variables, collected through questionnaires and local inspection. A hydrological service quality seal system was proposed: green, yellow, red and black, with green for properties with better quality and black with worse quality. The applied PAR allowed to establish a comparison between the properties, which allows decision makers to establish the priority order for the implementation of a PSH. The formulation for raising funds for the maintenance and management of the PSH program was based on applying a percentage on the water tariff and another on the sanitary sewage tariff, considering the user-payer principle. 13 percentages were simulated, based on different official rates, such as savings, SELIC, inflation and IPCA. For the payment for services, the equation considered, on the total collected, three installments: reserved for the administration of the PSH Program, reserve fund and effective amount to be used in payments, divided by the number of ha to be included in the PSH. It was considered that the areas of the properties that are likely to be incorporated into the PSH are areas with native vegetation in excess of those reserved, as permanent preservation. It can be concluded that the amounts to be paid to producers are compatible with the alternative value of corn and soybean production (traditional crops in the region), demonstrating that the potential to be collected for this basin, from water users, can compensate producers by not cultivating and releasing the areas for environmental preservation. These areas that are part of the PSH, therefore, become Environmental Assets.